Alternating panel charge sharing technique for touch screen panel self‐capacitance sensing IC. Issue 21 (4th September 2020) - Seong, S.; Lee, S.; Bae, S.; Lee, M.
Abstract : This Letter presents a self‐capacitance sensing (SCS) technique for touch screen panel with the alternating panel charge sharing (APCS) that effectively suppresses low‐frequency noise and achieves a better signal‐to‐noise ratio (SNR). With the proposed APCS‐based SCS, SNR is improved in measurement by 7.65 dB compared to the conventional panel charge sharing‐based SCS.